Changes in Cardiovascular Disease Risk Factors With Immediate Versus Deferred Antiretroviral Therapy Initiation Among HIV‐Positive Participants in the START (Strategic Timing of Antiretroviral Treatment) Trial. Issue 5 (May 2017) - Baker, Jason V.; Sharma, Shweta; Achhra, Amit C.; Bernardino, Jose Ignacio; Bogner, Johannes R.; Duprez, Daniel; Emery, Sean; Gazzard, Brian; Gordin, Jonathan; Grandits, Greg; Phillips, Andrew N.; Schwarze, Siegfried; et al.
Abstract : Introduction: HIV infection and certain antiretroviral therapy (ART) medications increase atherosclerotic cardiovascular disease risk, mediated, in part, through traditional cardiovascular disease risk factors. Methods and Results: We studied cardiovascular disease risk factor changes in the START (Strategic Timing of Antiretroviral Treatment) trial, a randomized study of immediate versus deferred ART initiation among HIV‐positive persons with CD4 + cell counts >500 cells/mm 3 . Mean change from baseline in risk factors and the incidence of comorbid conditions were compared between groups. The characteristics among 4685 HIV‐positive START trial participants include a median age of 36 years, a CD4 cell count of 651 cells/mm 3, an HIV viral load of 12 759 copies/mL, a current smoking status of 32%, a median systolic/diastolic blood pressure of 120/76 mm Hg, and median levels of total cholesterol of 168 mg/dL, low‐density lipoprotein cholesterol of 102 mg/dL, and high‐density lipoprotein cholesterol of 41 mg/dL. Mean follow‐up was 3.0 years. The immediate and deferred ART groups spent 94% and 28% of follow‐up time taking ART, respectively. Compared with patients in the deferral group, patients in the immediate ART group had increased total cholesterol and low‐density lipoprotein cholesterol and higher use of lipid‐lowering therapy (1.2%; 95% CI, 0.1–2.2). Concurrent increases in high‐density lipoprotein cholesterol with immediate ART resulted in a 0.1 lower total cholesterol to high‐density lipoprotein cholesterol ratio (95% CI, 0.1–0.2). Immediate ART resulted in 2.3% less BP‐lowering therapy use (95% CI, 0.9–3.6), but there were no differences in new‐onset hypertension or diabetes mellitus. Conclusions: Among HIV‐positive persons with preserved immunity, immediate ART led to increases in total cholesterol and low‐density lipoprotein cholesterol but also concurrent increases in high‐density lipoprotein cholesterol and decreased use of blood pressure medications. These opposing effects suggest that, in the short term, the net effect of early ART on traditional cardiovascular disease risk factors may be clinically insignificant." Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00867048.